2014
DOI: 10.1111/jpn.12267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L‐lysine on expression of selected genes, serum concentration of amino acids, muscle growth and performance of growing pigs

Abstract: Lysine (Lys) is the first limiting amino acid (AA) in most feed formulations for pigs and most abundant, along with leucine, in muscle proteins. An experiment was conducted with 17 pigs (17.7 ± 0.05 kg initial BW) to identify a role of dietary Lys in the control of protein synthesis in pigs. Fourteen pigs were randomly assigned to one of the two wheat-based dietary treatments: Lys-deficient, 3.0 g/kg (DEF) and Lys-adequate, 10.8 g/kg (ADE). Samples from jejunum mucosa, liver, Longissumus and Semitendinosus mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 30 publications
6
24
0
Order By: Relevance
“…Lysine is the most abundant amino acid in muscle proteins of the pig (Bikker et al, 1994). The greater mRNA expression of MyHC IIb in Logissimus muscle observed in gilts fed with different dietary digestible lysine contents support the hypothesis that lysine may stimulate, either direct or indirectly, the transcription of MyHC IIb (Morales et al, 2015).…”
Section: Discussion Mrna Expression Of Myhc Isoforms In Logissimus Musupporting
confidence: 52%
See 2 more Smart Citations
“…Lysine is the most abundant amino acid in muscle proteins of the pig (Bikker et al, 1994). The greater mRNA expression of MyHC IIb in Logissimus muscle observed in gilts fed with different dietary digestible lysine contents support the hypothesis that lysine may stimulate, either direct or indirectly, the transcription of MyHC IIb (Morales et al, 2015).…”
Section: Discussion Mrna Expression Of Myhc Isoforms In Logissimus Musupporting
confidence: 52%
“…The higher mRNA expression of MyHC IIb in Logissimus muscle caused by dietary DL content suggests that lysine stimulates the synthesis of skeletal muscle proteins at a transcriptional level (Morales et al, 2015). Lysine is the most abundant amino acid in muscle proteins of the pig (Bikker et al, 1994).…”
Section: Discussion Mrna Expression Of Myhc Isoforms In Logissimus Mumentioning
confidence: 99%
See 1 more Smart Citation
“…() and Morales et al. (). Hence, the results of the present experiment indicate that the presence of free Lys in duodenal digesta stimulates the expression of b 0,+ AT in the mucosa of duodenum.…”
Section: Discussionmentioning
confidence: 95%
“…Myosin heavy chain 4 (MYH4 or MyHC IIb) fibres are the most prominent in pigs and contribute to differential growth of muscles32. Furthermore, mRNA abundance of MyHC IIb can be used as an indicator of muscle protein synthesis and muscle growth rate3334. MyHC IIb is a type of fast fibre, and some studies have shown that the proportion of IIb glycolytic fibres is about 75–86% in commercial pig breeds that have a rapid growth rate35.…”
Section: Discussionmentioning
confidence: 99%